Measurement of amniotic fluid by ultrasonography. - Vásquez, Javier (2015)
Ultrasound measurement of amniotic fluid depth in milimeters is studied in 625 normal pregnant women, between 6 and 40 weeks of pregnancy, with normal and precise last menstrual period, single fetus with normal development and normal appearing placentas without early maturation. Depth varied from 15 to 74 mm between 6 and 20 week, increasing with age to 41 to 87mm in the second half of pregnancy. These findings corroborate those by other authors.